2020
DOI: 10.1080/19942060.2020.1724197
|View full text |Cite
|
Sign up to set email alerts
|

Sharp interface immersed boundary method for simulating three-dimensional swimming fish

Abstract: A second order finite-difference numerical method is used to solve the Navier-Stokes equations of incompressible flow, in which the solid body with complex geometry is immersed into the fluid domain with orthogonal Cartesian meshes. To account for influences of the solid body, interactive forces are applied as boundary conditions at Cartesian grid nodes located in the exterior but in the immediate vicinity of the solid body. Fluid flow velocities in these nodes are reconstructed to track and control the deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Some authors have employed inviscid methodologies to estimate the thrust and the power generated by swimming fish in high Reynolds numbers, such as the elongated body theory (EBT) proposed by Lighthill’s model [ 12 , 25 , 44 , 45 , 46 ]. However, some works have argued that the thrust is overestimated [ 15 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have employed inviscid methodologies to estimate the thrust and the power generated by swimming fish in high Reynolds numbers, such as the elongated body theory (EBT) proposed by Lighthill’s model [ 12 , 25 , 44 , 45 , 46 ]. However, some works have argued that the thrust is overestimated [ 15 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…This challenge becomes even more complex when trying to compute propulsive efficiency using the thrust generated by an undulating body, as it introduces the complication of distinguishing between thrust and drag forces within such a dynamic system [8,15]. Some authors have employed inviscid methodologies to estimate the thrust and the power generated by swimming fish in high Reynolds numbers, such as the elongated body theory (EBT) proposed by Lighthill's model [12,25,[44][45][46]. However, some works have argued that the thrust is overestimated [15,47].…”
Section: Introductionmentioning
confidence: 99%
“…Many research results on bionic underwater robot with multi tails have emerged in recent years. Cui et al [9] proposed a sharp interface immersion boundary method to simulate 3D swimming, which can accurately capture the geometry of deformation and interaction between moving bodies. Lucas et al [10] revealed that the airfoil like precursor of scads can generate negative pressure to reduce the forward resistance of fish and improve the propulsion efficiency.…”
Section: Introductionmentioning
confidence: 99%